Use of art as therapeutic intervention for enhancement of hand function in patients with rheumatoid arthritis: A pilot study - Sayali Khedekar; Apurv P Shimpi; Ashok Shyam; Parag Sancheti (Indian Journal of Rheumatology)
Background: Conventional physiotherapy treatment for patients with rheumatoid hand emphasizes on single-plane movements and strengthening exercises directed toward improvement of function and prevention of deformities. This may be nondirective and lacks creativity and hence may predispose to a high attrition from therapy. The current study aimed to evaluate the efficacy of art as a creative therapeutic procedure for enhancement of hand functions, self-perception, and quality of life in patients with rheumatoid arthritis (RA). Methods: A single-blinded, randomized controlled pilot study was conducted on 17 participants suffering from RA. The control group received conventional physiotherapy while the experimental group received art-based intervention with bimanual projects (viz., origami, paper quelling, clay modeling, and oil painting). Both groups received intervention for 45 min daily for 4 weeks. Pre- and post-interventional assessment was done using grip and pinch strength, Grip Ability Test (GAT), Jebsen–Taylor Hand Function Test (JHFT), Australian-Canadian Osteoarthritis Hand Index (AUSCAN), Michigan Hand Outcome Questionnaire (MHQ), and Health Assessment Questionnaire (HAQ). Results: There was an improvement in hand functions (grip strength [P = 0.042], two-point pinch strength [P = 0.039], three-point pinch strength [P = 0.043], GAT [P = 0.043], JHFT [P = 0.043]), self-perception (AUSCAN [P = 0.043], MHQ [P = 0.043]), and quality of life (HAQ;P = 0.043) in art therapy patients which was similar to conventional therapy patients. Conclusion: Art is an equally effective therapeutic intervention to conventional therapy for the enhancement of hand functions, self-perception, and quality of life in patients with RA.